Immigrants' disadvantage online: understanding the effects of immigration status, gender and country of origin on the e-government use in Israel. Issue 1 (2nd November 2020) - Rosenberg, Dennis
Abstract : Purpose: Digital inequality studies claim that social inequalities tend to be replicated online. However, studies have not attempted so far to deeper understand such stratification in immigrant societies regarding the e-government use. This study aims to understand the role of immigration status, gender and country of origin in the e-government use, thereby reflecting what the literature on the sociology of migration refers to as immigrants' "double" and "triple" disadvantage. Design/methodology/approach: Israel was chosen as a case study because it is an immigration society in which immigrants' socioeconomic status is usually inferior to that of the native population. The data were attained from the 2017 Israel Social Survey. The population of the study included internet users from the Jewish sector (N = 4, 222). Logistic regression was used as the multivariate technique. Findings: The results indicated that immigrant women are disadvantaged in terms of e-government use regardless of their year of immigration. Yet, when the data are segmented by country of origin, only female immigrants from the former Soviet Union show evidence of a triple disadvantage. Research limitations/implications: The conclusion is that immigrants' disadvantages in the offline sphere also exist in the online sphere. Practical implications: Particular categories, which use e-government to a small extent, were identified, serving a call for action for the public officials. They should develop plans to make e-government more accessible to individuals belonging to these categories. Originality/value: This study incorporates digital and immigrant sociology for the explanation of immigrants' (online) social inclusion.